2022
DOI: 10.1038/s41598-022-11156-1
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide risk to managed bees during blueberry pollination is primarily driven by off-farm exposures

Abstract: When managed bee colonies are brought to farms for crop pollination, they can be exposed to pesticide residues. Quantifying the risk posed by these exposures can indicate which pesticides are of the greatest concern and helps focus efforts to reduce the most harmful exposures. To estimate the risk from pesticides to bees while they are pollinating blueberry fields, we sampled blueberry flowers, foraging bees, pollen collected by returning honey bee and bumble bee foragers at colonies, and wax from honey bee hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 99 publications
2
19
0
Order By: Relevance
“…The lack of significant negative effects following fungicide product exposure with and without M. plutonius infection are not surprising, as other researchers also have not found significant negative effects on honey bee larval survival from oral (or contact) exposure to field-relevant concentrations of the active fungicide ingredients in Captan, Luna, and Switch (Everich et al, 2009;Wood et al, 2020). While our highest tested concentrations of the active ingredients in Captan, Luna, and Switch reflected the highest reported residues of these active ingredients in pollen/bee bread and honey (Graham et al, 2021(Graham et al, , 2022Rondeau and Raine, 2022), the transfer rate of residues from pollen into royal jelly and worker jelly is believed to be low (Bohme et al, 2018(Bohme et al, , 2019Milone et al, 2021), and thus, our concentrations are likely an over estimation of exposure. Although most fungicides detected in honey have systemic properties, fludioxonil is a non-systemic fungicide and its residues have never been reported in honey (Rondeau and Raine, 2022), therefore we used residue concentrations for pollen/bee bread in place of honey.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The lack of significant negative effects following fungicide product exposure with and without M. plutonius infection are not surprising, as other researchers also have not found significant negative effects on honey bee larval survival from oral (or contact) exposure to field-relevant concentrations of the active fungicide ingredients in Captan, Luna, and Switch (Everich et al, 2009;Wood et al, 2020). While our highest tested concentrations of the active ingredients in Captan, Luna, and Switch reflected the highest reported residues of these active ingredients in pollen/bee bread and honey (Graham et al, 2021(Graham et al, , 2022Rondeau and Raine, 2022), the transfer rate of residues from pollen into royal jelly and worker jelly is believed to be low (Bohme et al, 2018(Bohme et al, , 2019Milone et al, 2021), and thus, our concentrations are likely an over estimation of exposure. Although most fungicides detected in honey have systemic properties, fludioxonil is a non-systemic fungicide and its residues have never been reported in honey (Rondeau and Raine, 2022), therefore we used residue concentrations for pollen/bee bread in place of honey.…”
Section: Discussionsupporting
confidence: 69%
“…Although most fungicides detected in honey have systemic properties, fludioxonil is a non-systemic fungicide and its residues have never been reported in honey (Rondeau and Raine, 2022), therefore we used residue concentrations for pollen/bee bread in place of honey. As residue concentrations in pollen/bee bread are many folds higher than concentrations found in nectar/honey (Graham et al, 2021(Graham et al, , 2022Rondeau and Raine, 2022), this again illustrates our tested concentrations as a potential over exposure. On the other hand, water is also an important constituent in worker larval diet (McCune et al, 2021).…”
Section: Discussionmentioning
confidence: 53%
“…However, we know less about the resulting pesticide risk, especially between bee species and in different landscape contexts (but see refs. 22 , 26 , 46 , 47 ). We found that increasing the proportion of agricultural land increased the risk for B. terrestris and O. bicornis but not for A. mellifera .…”
Section: Discussionmentioning
confidence: 99%
“…For example, crops such as corn or soybean are commonly grown with neonicotinoid-coated seeds and subsequent herbicide use (e.g., glyphosate) in spring . In a landscape with more crop types and a greater diversity of pesticides applied, pesticide exposure is less predictable since honey bees can forage up to 10 km and come into contact with different types of pesticides simultaneously in surrounding landscapes. ,, In these landscapes with more diverse crops and varying pesticide uses, the development of detoxification solutions may be more complicated. ,, Beekeepers, especially commercial operators managing thousands of bee hives located in different apiary locations, face more uncertainties regarding detoxification strategies . While one constituent in a 3P treatment usually works to detoxify one set of pesticides, the challenge presented by complex exposure situations will not be resolved until a product composed of diverse constituents is developed to detoxify different pesticides …”
Section: Impact Of Gut Hive and Landscape Environment And Bee Sociali...mentioning
confidence: 99%
“…70 In a landscape with more crop types and a greater diversity of pesticides applied, pesticide exposure is less predictable since honey bees can forage up to 10 km and come into contact with different types of pesticides simultaneously in surrounding landscapes. 66,76,77 In these landscapes with more diverse crops and varying pesticide uses, the development of detoxification solutions may be more complicated. 66,76,77 Beekeepers, especially commercial operators managing thousands of bee hives located in different apiary locations, face more uncertainties regarding detoxification strategies.…”
Section: Environment and Bee Sociality On The Development And Applica...mentioning
confidence: 99%